Specific features to differentiate Giant cell arteritis aortitis from aortic atheroma using FDG-PET/CT - Olivier Espitia (Nature Portfolio, 2021)
Abstract Aortic wall 18F-fluorodeoxyglucose (FDG)-uptake does not allow differentiation of aortitis from atheroma, which is problematic in clinical practice for diagnosing large vessel vasculitis giant-cell arteritis (GCA) in elderly patients. The purpose of this study was to compare the FDG uptake characteristics of GCA aortitis and aortic atheroma using positron emission tomography/FDG computed tomography (FDG-PET/CT). This study compared FDG aortic uptake between patients with GCA aortitis and patients with aortic atheroma; previously defined by contrast enhanced CT. Visual grading according to standardized FDG-PET/CT interpretation criteria and semi-quantitative analyses (maximum standardized uptake value (SUVmax), delta SUV (∆SUV), target to background ratios (TBR)) of FDG aortic uptake were conducted. The aorta was divided into 5 segments for analysis. 29 GCA aortitis and 66 aortic atheroma patients were included. A grade 3 FDG uptake of the aortic wall was identified for 23 (79.3%) GCA aortitis patients and none in the atheroma patient group (p < 0.0001); grade 2 FDG uptake was as common in both populations. Of the 29 aortitis patients, FDG uptake of all 5 aortic segments was positive for 21 of them (72.4%, p < 0.0001). FDG uptake of the supra-aortic trunk was identified for 24 aortitis (82.8%) and no atheromatous cases (p < 0.0001). All semi-quantitative analyses of FDG aortic wall uptake (SUVmax, ∆SUV and TBRs) were significantly higher in the aortitis group. ∆SUV was the feature with the largest differential between aortitis and aortic atheroma. In this study, GCA aortitis could be distinguished from an aortic atheroma by the presence of an aortic wall FDG uptake grade 3, an FDG uptake of the 5 aortic segments, and FDG uptake of the peripheral arteries.